2014
DOI: 10.3390/ijms150917130
|View full text |Cite
|
Sign up to set email alerts
|

High-Dose Diosgenin Reduces Bone Loss in Ovariectomized Rats via Attenuation of the RANKL/OPG Ratio

Abstract: The aim of this study was to evaluate effect of diosgenin (DG) on rats that had osteoporosis-like features induced by ovariectomy (OVX). Seventy-two six-month-old female Wistar rats were subjected to either ovariectomy (n = 60) or Sham operation (SHAM group, n = 12). Beginning at one week post-ovariectomy, the OVX rats were treated with vehicle (OVX group, n = 12), estradiol valerate (EV group, n = 12), or DG at three doses (DG-L, -M, -H group, n = 12, respectively). After a 12-week treatment, administration o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
39
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 42 publications
6
39
0
Order By: Relevance
“…Low concentrations of diosgenin increased proliferation and stimulated the synthesis and secretion of type 1 collagen, alkaline phosphatase and osteopontin in murine osteoblastic MC3T3-E1 cells, although at a higher concentration (10 μM) diosgenin was cytotoxic (Alcantara et al, 2011). Consistently, Zhang et al (2014a) demonstrated the decrease in bone formation indices after a larger diosgenin dose in vivo. It is possible that diosgenin may stimulate bone formation through activation of angiogenesis in bone.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…Low concentrations of diosgenin increased proliferation and stimulated the synthesis and secretion of type 1 collagen, alkaline phosphatase and osteopontin in murine osteoblastic MC3T3-E1 cells, although at a higher concentration (10 μM) diosgenin was cytotoxic (Alcantara et al, 2011). Consistently, Zhang et al (2014a) demonstrated the decrease in bone formation indices after a larger diosgenin dose in vivo. It is possible that diosgenin may stimulate bone formation through activation of angiogenesis in bone.…”
Section: Discussionmentioning
confidence: 72%
“…Moreover, the long-term (12-week) treatment with diosgenin at a high dose of 96 mg/kg p.o. daily in 6-month-old ovariectomized rats counteracted the effects of estrogendeficiency on bone mineral density and trabecular bone histomorphometry, decreasing the RANKL/osteoprotegerin ratio (assessed by immunohistochemistry and in situ hybridization; Zhang et al, 2014a).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thirty of the these rats were randomly allocated to low (10 mg/kg), middle (30 mg/kg), and high (90 mg/kg) dose-treated groups with administration of three doses of diosgenin (National Institute for the Control of Pharmaceutical and Biological Products, Beijing, China), respectively, by oral gavage for another 14 days. The doses of diosgenin are similar to 1 time, 2 times, and 4 times dose of steroidal saponins in clinical prescription for treatment of patients with myocardial ischemia or coronary heart disease (1.44 g/60 kg weight/-day) [23]. Others feed with 0.5 % 70 mg/kg sodium carboxymethylcellulose (CMC-Na, Longhe food ingredient co., LTD, Nanjing, China) were defined as model group.…”
Section: Animal Groupingmentioning
confidence: 99%
“…However the mechanism of action is still not clear but can be associated with a modulation on the receptor activator of NF-kB ligand/osteoprotegerin ratio [80]. …”
Section: Pharmacology: Recent Datamentioning
confidence: 99%